THE PRACTICE OF FAIR TRANSACTION ON PROPERTY BUSINESS: A CASE ON ISLAMIC PROPERTY COMPANY - Lailatul Azizah (Universitas Airlangga, 2022)
Pasuruan which is known as an industrial area (PIER) open up opportunity of many investors to invest capital in the field. This condition brought positive impacts like availability of job opportunities for workers both local and migrants settled in Pasuruan. But on the other hand there is a problem of housing needs. Property Syariah is a kind of business opportunity engaged in the sale and purchase of plots of land (houses) as a solution for the surrounding community with the concept of financing without, exploitating customer, making it easier for consumers to invest both for business and residential. This research used qualitative method using case study approach. This reseach deliver condition of property business and analyzed comprehensively according to Islamic financing policies. From the beginning of data analysis, it can be seen that the sale and purchase of land plots of Aflaha Property Syariah is facing the threat of emerging competition in the existing financing business, both conventional and sharia. Steps that need to be taken include further increasing customer satisfaction, through murabahah contracts, ijarah muntahiya bit – tamlik and musyarakah contracts, mutanaqishah by accelerating the process of obtaining certificates (proof of ownership of land and shop houses) however still applying the principle of ta'awun in their buying and selling activities. This research bring an empirical study of fair transactions on property business which can be input for future related research and bring any recommendation for related parties.